Salivary MicroRNAs: Diagnostic Markers of Mild Traumatic Brain Injury in Contact-Sport - Di Pietro, Valentina; Porto, Edoardo; Ragusa, Marco; Barbagallo, Cristina; Davies, David; Forcione, Mario; Logan, Ann; Di Pietro, Cinzia; Purrello, Michele; Grey, Michael; Hammond, Douglas; Sawlani, Vijay; et al. (Frontiers in Molecular Neuroscience, 2018)
Concussion is difficult to diagnose, particularly when and symptoms are atypical or late in presenting. An accurate and timely initial assessment is crucial for clinical management. Cerebral spinal fluid (CSF) and blood markers of traumatic brain injury show promising results but their clinical applicability in concussion has significant limitations. In the study, we explored saliva as a new source of biomarkers of concussion. Saliva samples of concussed players were collected after 48-72 hours from concussion and analyzed by high-throughput technologies. A discovery group of 10 concussed rugby/football professional and semiprofessional athletes and 10 non-concussed matched controls was used for the analysis of 92 inflammatory proteins by the Proseek-Multiplex-Inflammation technology. In addition, saliva samples of 6 concussed and 6 non-concussed athletes were used to screen 800 human microRNAs (miRNAs) by the Nanostring technology. The results were then validated by RT-qPCR in an enlarged cohort (validation group) comprising 22 concussed athletes. Results showed, no significant variations of the 65 inflammatory proteins detected in saliva between groups but 5 microRNAs, miR-27b-3p (p=0.016), let-7i-5p (p=0.001), miR-142-3p (p=0.008), miR-107 (p=0.028), miR-135b-5p (p=0.017) significantly upregulated in concussed athletes. Univariate ROC curve analysis showed that the differentially expressed miRNAs could be considered good classifiers of concussion. Further analyses showed significant correlation between these microRNAs and Reaction Time component of the ImPACT concussion assessment tool. In addition, biocomputation analysis predicted the involvement of these microRNAs in important biological processes that might be related to trauma, such as response to hypoxia, cell death, neurogenesis, axon repair and myelination. Ease of access and non-invasiveness of saliva samples make these biomarkers particularly suitable for concussion assessment.